2018
DOI: 10.1080/10245332.2018.1491093
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis in adults and adolescents—a life-threatening disease: analysis of 133 cases from a single center

Abstract: DEP/L-DEP was a good salvage treatment. L-DEP might be a more effective first-line initial regimen than HLH-94/04 regimen for EBV-HLH. Finally, allo-HSCT is an effective radical treatment for EBV-HLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 25 publications
1
42
0
2
Order By: Relevance
“…In one Japanese cohort, allo-HSCT resulted in an 85.7% 10-year OS for patients with EBV-HLH [20]. In a retrospective analysis from our centre, 27.1% of patients with EBV-HLH received allo-HSCT, and the nal survival rate was 52.78% [21]. However, some patients in the actual situation are unable to receive allo-HCST due to various factors.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In one Japanese cohort, allo-HSCT resulted in an 85.7% 10-year OS for patients with EBV-HLH [20]. In a retrospective analysis from our centre, 27.1% of patients with EBV-HLH received allo-HSCT, and the nal survival rate was 52.78% [21]. However, some patients in the actual situation are unable to receive allo-HCST due to various factors.…”
Section: Discussionmentioning
confidence: 92%
“…Among the infections-associated HLH, Epstein-Barr virus (EBV) infection-associated HLH (EBV-HLH) is one of the most common. In previous studies, EBV-HLH patients suffered a much worse prognosis than patients with other types of infection-associated HLH, especially in adult HLH patients [3][4][5]. In 2015, a study of 61 cases with EBV-HLH reported a 1-year overall survival (OS) of only 25.0% [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…will not respond to HLH-94 [7]. In a study of adults and adolescents EBV-HLH 133 patients, the nonresponse rate of HLH-94 regimen is 52% [5]. Our center's DEP (doxorubicin-etoposidemethylprednisolone) regimen and L-DEP (PEG-aspargase and DEP regimen combination) as the salvage therapy for refractory EBV-HLH achieve a much better overall response rate and increase the chance to receive allo-HSCT, which improves survival [8][9][10].…”
Section: Introductionmentioning
confidence: 96%
“…Among the infection associated HLH, Epstein-Barr virus (EBV) infection associated HLH (EBV-HLH) is one of the most common. In previous studies, EBV-HLH patients suffer a much worse prognosis than other type of infection associated HLH, especially in adult HLH patients [3][4][5]. A previous study of 61 cases of EBV-HLH in 2015, reported a 1year overall survival (OS) of only 25.0% [6].…”
Section: Introductionmentioning
confidence: 99%